A Non Uniform Bound on Normal Approximation of Randomized Orthogonal Array Sampling Designs via Stein’s Method - Nahathai Rerkruthairat (Science Faculty of Chiang Mai University, 2019)
The randomized orthogonal array sampling design is used in many fileds, such as system testing in computer science and experiment design in statistics, when a group of examples or inputs for testing are needed. In this paper, Stein’s method is used to investigate a non uniform bound on normal ap-proximation of the randomized orthogonal array sampling design. Assuming the finiteness of the moment, the rate of this convergence is sharper than the previous results.